The Philippines : Accounting and Auditing - World Bank (Washington, DC, 2013)
Historically, accounting and auditing in the Philippines has been heavily influenced by practices of the United States. More recently, efforts have been made to adapt International Accounting Standards and International Standards on Auditing to national circumstances. However, there are gaps between the current international standards and the applicable Philippine standards, and in compliance of Philippine standards. Established in 1929, the Philippine Institute of Certified Public Accountants (PICPA) is one of the oldest professional accountancy bodies in Asia. The passage of the Accountancy Act 1923 led to the creation of the Board of Accountancy, with authority to issue certificates for certified public accountants. The PICPA presently lacks effective mechanisms either for monitoring members' professional activities or for taking appropriate actions against errant members. There are gaps in the capacity of the SEC and the Central Bank to monitor and enforce rules and regulations with reference to accounting, auditing, and financial reporting by the enterprises under their regulatory authority. The Board of Accountancy, under the Professional Regulation Commission, has the authority and responsibility to regulate the accounting profession, but is handicapped by lack of resources. Policy recommendations to improve accounting and auditing practices in the Philippines were discussed and agreed by a group of national stakeholders at the conclusion of the accounting and auditing review exercise conducted in May - June 2001, under the joint World Bank-IMF Reports on the Observance of Standards and Codes (ROSC) initiative.